How to use Photos for Mac - Grothaus, Michael (Que, 2016)
"How to Use Photos for Mac is an easy-to-understand, but comprehensive, 3+ hour video course that introduces viewers to the Photos for Mac application, it's interface and tools, and then explains exactly how to use this powerful application on a Mac running OS X El Capitan. In non-technical, non-geeky terms, Michael Grothaus guides viewers step-by-step through organizing, editing, and sharing their photos using Photos for Mac."--Resource description page.